Privacy and pubblicità - Davide Tommaso Ferrando (ARQ)
Berlusconi’s 1994 campaign video, recorded in an improvised studio, staged a domestic setting to project his political persona. By 2023, as his influence waned, his private life became fodder for social media, transforming intimacy into a public spectacle. The shifting nature of these spaces speaks to the broader impact of digital media on the private interior, where the home itself has evolved into a post-domestic stage for public performance.